2018
DOI: 10.23876/j.krcp.2018.37.3.266
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum mineral parameters with mortality in hemodialysis patients: Data from the Korean end-stage renal disease registry

Abstract: BackgroundWe investigated the associations between mineral metabolism parameters and mortality to identify optimal targets in Korean hemodialysis patients.MethodsAmong hemodialysis patients registered in the end-stage renal disease registry of the Korean Society of Nephrology between March 2012 and June 2017, those with serum calcium, phosphorus, and intact parathyroid hormone (iPTH) measured at enrollment were included. Association of serum levels of calcium, phosphorus, and iPTH with all-cause mortality was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…It is well known that most patients with chronic kidney disease (CKD) show a progressive deterioration in mineral homeostasis. These changes have been associated with a complex state termed CKD-mineral and bone disorder (CKD-MBD), which can exhibit fragility fractures, vascular calcification, and cardiovascular disease or mortality (1)(2)(3)(4). As the renal function declines, the ability of the kidneys to appropriately excrete a phosphate load is reduced leading to hyperphosphatemia, elevated parathyroid hormone (PTH), and decreased calcitriol with the associated elevations in the levels of fibroblast growth factor-23 (FGF-23) (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that most patients with chronic kidney disease (CKD) show a progressive deterioration in mineral homeostasis. These changes have been associated with a complex state termed CKD-mineral and bone disorder (CKD-MBD), which can exhibit fragility fractures, vascular calcification, and cardiovascular disease or mortality (1)(2)(3)(4). As the renal function declines, the ability of the kidneys to appropriately excrete a phosphate load is reduced leading to hyperphosphatemia, elevated parathyroid hormone (PTH), and decreased calcitriol with the associated elevations in the levels of fibroblast growth factor-23 (FGF-23) (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Most epidemiologic studies reported that higher serum iPTH level is associated with increased all-cause mortality in dialysis patients [1][2][3]. However, the impact of iPTH level on mortality is controversial in dialysis patients [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Also noteworthy is that dietary sources of phosphorus in Korean hemodialysis patients may differ from those of other countries. Nonetheless, we believe the study by Kim et al [1] provides insight that could help reduce the burden of hyperphosphatemia, a common problem among dialysis populations throughout the world.…”
mentioning
confidence: 97%
“…We read the paper entitled “Association of serum mineral parameters with mortality in hemodialysis patients: Data from the Korean end-stage renal disease registry” by Kim et al [1] with great interest. Using data from the nationwide Korean Society of Nephrology ESRD Registry, the authors revealed that high serum calcium, low phosphorus, and both high and low intact parathyroid hormone levels were associated with increased all-cause mortality.…”
mentioning
confidence: 99%
See 1 more Smart Citation